Implementation of FOC algorithm using FPGA for GaN-based three phase induction motor drive - Tung Duong Do; Nam Duong Le; Vu Hoang Phuong; Nguyen Tung Lam (Institute of Advanced Engineering and Science, 2022)
Induction motor is widely used in industrial applications due to its low cost, simple design, and reliability. In this paper, the induction motor control structure FOC will be implemented on the FPGA platform for the drive system using GaN devices. By using GaN technology, the switching frequency can be up to 100 kHz instead of 2 to 20 kHz when using IGBT transistors. It leads to a significant reduction in switching loss as well as increasing the power density of the power electronic converter. The control structure will be programmed in VHDL language on the system-on-chip environment of Xilinx Zybo z7010 FPGA development board. The validity of the research is verified by some results when operating with HIL device.